The alpha sequence of the cytomegalovirus genome functions as a cleavage/packaging signal for herpes simplex virus defective genomes. - Spaete, R R (1985)
Although herpes simplex virus (HSV) 1 and human cytomegalovirus (CMV) differ remarkably in their biological characteristics and do not share nucleotide sequence homology, they have in common a genome structure that undergoes sequence isomerization of the long (L) and short (S) components. We have demonstrated that the similarity in their genome structures extends to the existence of an alpha sequence in the CMV genome as previously defined for the HSV genome. As such, the alpha sequence is predicted to participate as a cis-replication signal in four viral functions: (i) inversion, (ii) circularization, (iii) amplification, and (iv) cleavage and packaging of progeny viral DNA. We have constructed a chimeric HSV-CMV amplicon (herpesvirus cis replication functions carried on an Escherichia coli plasmid vector) substituting CMV DNA sequences for the HSV cleavage/packaging signal in a test of the ability of this CMV L-S junction sequence to provide the cis signal for cleavage/packaging in HSV 1-infected cells. We demonstrate that the alpha sequence of CMV DNA functions as a cleavage/packaging signal for HSV defective genomes. We show the structure of this sequence and provide a functional demonstration of cross complementation in replication signals which have been preserved over evolutionary time in these two widely divergent human herpesviruses.